2018
DOI: 10.3389/fphar.2018.01021
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Anti-IL17 on Acute Lung Injury Induced by LPS in Mice

Abstract: Introduction: T helper 17 (Th17) has been implicated in a variety of inflammatory lung and immune system diseases. However, little is known about the expression and biological role of IL-17 in acute lung injury (ALI). We investigated the mechanisms involved in the effect of anti-IL17 in a model of lipopolysaccharide (LPS)-induced acute lung injury (ALI) in mice.Methods: Mice were pre-treated with anti-IL17, 1h before saline/LPS intratracheal administration alongside non-treated controls and levels of exhaled n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 65 publications
1
42
0
Order By: Relevance
“…Our study showed that ERM, albeit not JSM or PC, induced IL-10 and decreased TNF and IL-17. Importantly, a recent study showed that anti-IL-17 pretreatment protects mice from the acute lung injury (59). These antiinflammatory effects of ERM are dependent on DEL-1 and, at least in part, on its anti-neutrophil recruitment action.…”
Section: Figure 5 Erm Reverses Il-17-mediated Suppression Of Del-1 Bmentioning
confidence: 99%
“…Our study showed that ERM, albeit not JSM or PC, induced IL-10 and decreased TNF and IL-17. Importantly, a recent study showed that anti-IL-17 pretreatment protects mice from the acute lung injury (59). These antiinflammatory effects of ERM are dependent on DEL-1 and, at least in part, on its anti-neutrophil recruitment action.…”
Section: Figure 5 Erm Reverses Il-17-mediated Suppression Of Del-1 Bmentioning
confidence: 99%
“…The use of IL-17 antibody is well-recognized; it is currently approved in the treatment of psoriatic arthritis. Moreover, the therapeutic role of IL-17 antibodies has already been established not only in different cancer types 16 but also in the treatment of lung infection with H1N1 virus, 19 in acute respiratory distress syndrome, 4,20 and pulmonary fibrosis. 21 From this analysis, and in the context of the global pandemic, there seem to be some theoretical elements to testing the potential utility of IL-17 antibodies in patients with lung cancer and COVID-19 in a clinical trial setting, with its potentially high social impact and given the lack of specific validated treatments.…”
Section: Potential Role Of Il-17 Antibody In the Treatment Of Patientmentioning
confidence: 99%
“…Anti-IL-17A humanized monoclonal antibodies such as secukinumab (AIN457) (approved fully human IL-17-specific IgG1k monoclonal antibody) and Ixekizumab (LY2439821) (under a phase III clinical trial for psoriasis) are well-known and recognized treatment options for psoriasis. 44,[59][60][61] These anti-IL-17A monoclonal antibodies are also utilized in different inflammatory diseases, including ARDS, 13 rheumatism, 61 and pulmonary fibrosis. 62 Moreover, patients presenting with COVID-19 show elevated serum IL-6, which correlates with respiratory failure.…”
Section: Il-17a Targeting As a Treatment Strategy Against Covid-19mentioning
confidence: 99%
“…10,11 In turn, IL-17A acts by activating inducible nitric oxide synthase (iNOS) and inducing the expression of macrophages, IL-1β, IL-6, IL-8, TNFα, and several chemokines, which collaborate to potentiate the inflammatory process of ARDS. 13 Elevated Th17 (as well as Th1) responses or enhanced IL-17-related pathways are also observed in MERS-CoV and SARS-CoV patients. 14,18 ARDS is not commonly due to the viral load but due to an exuberant immune response, and results in cytokine release syndrome (CRS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation